Online Learning and Face-to-Face Learning in the COVID-19 Pandemic in SMA Erlangga Pematangsiantar - Ahmad Fakhri Hutauruk; Sariaman Gultom; Ahmad Arif Budiman Nasution (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to explore online and face-to-face learning (class) so that it can be effective, and the curriculum objectives are met. The nature of this research is qualitative phenomenology to be able to find out the extent of the application of learning that has been carried out online and face-to-face at SMA Erlangga Pematangsiantar, North Sumatera. The research mechanism includes the planning, implementation, observation, and reflection stages. The research results found several obstacles in terms of implementation but in general, the teacher can overcome them well. During a pandemic, a teacher's creativity is highly tested by the learning he does both in online and face-to-face systems so that learning success can be achieved. Finally, this research gives the result that by comparing the learning system, the teacher actually wants direct (face-to-face) pursuit so that it is easier in the process of interactive communication with students, and student motivation also increases in classroom learning because of direct interaction.